Conditional knockout of kisspeptin signaling in brown adipose tissue increases metabolic rate and body temperature and lowers body weight - Tolson, Kristen P. (FASEB J, 2019)
The peptide kisspeptin and its receptor, Kiss1r, act centrally to stimulate reproduction. Evidence indicates that kisspeptin signaling is also important for body weight (BW) and metabolism. We recently reported that Kiss1r KO mice develop obesity, along with reduced metabolism and energy expenditure, independent of estradiol levels. Outside the brain, Kiss1r is expressed in several metabolic tissues, including brown adipose tissue (BAT), but it is unknown which specific tissue is responsible for the metabolic phenotype in Kiss1r KOs. We first determined that global Kiss1r KO mice have significant alterations in body temperature and BAT thermogenic gene expression, perhaps contributing to their obesity. Next, to test whether kisspeptin signaling specifically in BAT influences BW, metabolism, or body temperature, we used Cre/ lox technology to generate conditional Kiss1r knockout exclusively in BAT (BAT-Kiss1r KO). Unlike global Kiss1r KOs, BAT-Kiss1r KOs (lacking Kiss1r in just BAT) were not hypogonadal, as expected. Surprisingly, however, BAT-Kiss1r KOs of both sexes displayed significantly lower BW and adiposity than controls. This novel BAT-Kiss1r KO phenotype was of greater magnitude in females and was associated with improved glucose tolerance, increased metabolism, energy expenditure, and locomotor activity, along with increased body temperature and BAT gene expression, specifically Cox8b. Our findings suggest that the previously observed obesity and decreased metabolism in global Kiss1r KOs reflect impaired kisspeptin signaling in non-BAT tissues. However, the novel finding of increased metabolism and body temperature and lower BW in BAT-Kiss1r KOs reveal a previously unidentified role for endogenous kisspeptin signaling in BAT in modulating metabolic and thermogenic physiology.